#7x + 3(2x-6) = 3x + 8#

First, distribute #3(2x-6)# using the distributive property:

Following this image, we know that the expression will simplify to:

#(3 * 2x) + (3 * -6)#

#=> 6x - 18#

Let's put this back into the equation:

#7x + 6x - 18 = 3x + 8#

Now combine like terms on the left side of the equation:

#13x - 18 = 3x + 8#

Now subtract #color(blue)(3x)# on both sides of the equation:

#13x - 18 quadcolor(blue)(-quad3x) = 3x + 8 quadcolor(blue)(-quad3x)#

#10x - 18 = 8#

Add #color(blue)(18)# to both sides of the equation:

#10x - 18 quadcolor(blue)(+quad18) = 8 quadcolor(blue)(+quad18)#

#10x = 26#

Divide both sides by #color(blue)10#:

#(10x)/color(blue)10 = 26/color(blue)10#:

#x = 26/10#

Divide numerator and denominator by #color(blue)2#:

#x = 26/10 color(blue)(-: 2/2)#

So the final answer is:

#x = 13/5#

Hope this helps!